What Courses Teach Artificial Intelligence in Medicine? A Guide for Professionals - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into healthcare is rapidly transforming clinical practice, research, and patient care. For professionals and th...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care